Plan de contingencia de los equipos y sistemas informáticos en el gobierno autónomo descentralizado municipal del cantón Junín - Palacios Pacheco, Raúl Alejandro (2013)
In order for the Municipal Autonomous Decentralized Government of Junín have an contingency plan for equipment and systems, it was performed the analysis, detection, evaluation and prioritization of potential threats that may suffer the institution and at same time prioritized relevance and important to the organization. To achieve this purpose MAGERIT was used because it is a Methodology of Risk Analysis and Management Information Systems, which is directly related to the widespread use of electronic, computer and telematics. The final product contributes to the institution known vulnerabilities and thus achieves to protect the integrity of information and physical and logical components.